2014
DOI: 10.1016/j.neuroimage.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Structural network analysis of brain development in young preterm neonates

Abstract: Preterm infants develop differently than those born at term and are at higher risk of brain pathology. Thus, an understanding of their development is of particular importance. Diffusion tensor imaging (DTI) of preterm infants offers a window into brain development at a very early age, an age at which that development is not yet fully understood. Recent works have used DTI to analyze structural connectome of the brain scans using network analysis. These studies have shown that, even from infancy, the brain exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 52 publications
12
82
1
Order By: Relevance
“…With all major white matter tracts being in place by the end of normal gestation, it is not surprising that structural connectome studies -examining whole brain connectivity on a macroscopic level (Box 1) -have revealed structural network organization in the neonatal brain to show great similarity to the adult human brain Brown et al, 2014;Ratnarajah et al, 2013;Shi et al, 2012;Tymofiyeva et al, 2012;van den Heuvel et al, 2014;Yap et al, 2011). Key features of adult connectome architecture have been demonstrated in the neonatal brain, including a small world organization -combining local specialization with long-range efficiency -, a modular topology -meaning that the network constitutes smaller subnetworks for specialized information processing -, and a heavy tailed degree distribution with brain regions which show the highest number of connections forming a central core or 'rich club' (Box 1).…”
Section: Postnatal Brain Developmentmentioning
confidence: 99%
“…With all major white matter tracts being in place by the end of normal gestation, it is not surprising that structural connectome studies -examining whole brain connectivity on a macroscopic level (Box 1) -have revealed structural network organization in the neonatal brain to show great similarity to the adult human brain Brown et al, 2014;Ratnarajah et al, 2013;Shi et al, 2012;Tymofiyeva et al, 2012;van den Heuvel et al, 2014;Yap et al, 2011). Key features of adult connectome architecture have been demonstrated in the neonatal brain, including a small world organization -combining local specialization with long-range efficiency -, a modular topology -meaning that the network constitutes smaller subnetworks for specialized information processing -, and a heavy tailed degree distribution with brain regions which show the highest number of connections forming a central core or 'rich club' (Box 1).…”
Section: Postnatal Brain Developmentmentioning
confidence: 99%
“…Previous reports have demonstrated the degree of prematurity at birth was associated with a reduction in density and lower global efficiency in children born very preterm, suggesting that brain networks are less connected and less complex [7, 8]. However, it remains unclear whether the altered structural brain connectivity is affected by prematurity itself or by adverse neonatal conditions encountered during the hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…SMOTE with different costs (SDC) is a variant of SMOTE, improved to better handle imbalanced classes [1]. For SDC, we set K = 1 as it was found to give highest accuracy over range [1,5]. For PCA, once the variation modes were learned, new instances were generated by sampling the Gaussian distribution defined by the variation modes.…”
Section: Resultsmentioning
confidence: 99%
“…Each connectome was constructed by grouping tracts according to their endpoint regions. Following [5], we constructed three connectome types for each scan, including a mean-FA weighted connectome, a tract-count connectome and a normalized tract-count connectome. Network measures summarizing the connectome's topological properties were computed for each connectome type.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation